2020
DOI: 10.3389/fphys.2020.00846
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: PRDM16 Upregulation Induced by MicroRNA-448 Inhibition Alleviates Atherosclerosis via the TGF-β Signaling Pathway Inactivation

Abstract: The dysregulated expression of microRNAs (miRs) has been associated with pathological and physiological processes of atherosclerosis (AS). In addition, PR domain-containing 16 (PRDM16), a transcriptional mediator of brown fat cell identity and smooth muscle cell activities, may be involved in the hypercholesterolemia during development of AS. The bioinformatic analysis identified a regulatory miR-448 of PRDM16. Hence, the current study aimed to explore whether miR-448 influenced the activities of aortic smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, PRDM16 is enriched in GTEx arterial tissues and was identified as a key driver gene in STARNET artery tissue, consistent with our scATAC data. PRDM16 regulates TGF-beta signaling 84 through direct interactions with Smad 85 and SKI 86 proteins, both of which are associated with CAD 13 . PRDM16 may play key roles in endothelial cells in arterial flow recovery 87 .…”
Section: Discussionmentioning
confidence: 99%
“…However, PRDM16 is enriched in GTEx arterial tissues and was identified as a key driver gene in STARNET artery tissue, consistent with our scATAC data. PRDM16 regulates TGF-beta signaling 84 through direct interactions with Smad 85 and SKI 86 proteins, both of which are associated with CAD 13 . PRDM16 may play key roles in endothelial cells in arterial flow recovery 87 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a review of various publications, it seems that the approaches used to search for markers for the diagnosis and treatment of atherosclerosis, including miRNA, have not yet solved the problem of diagnosing and treating atherosclerosis (Chen et al, 2020;Ryu et al, 2020;Sun et al, 2020;You et al, 2020). In human, it is known about 7000 miRNA and more than 20,000 genes, and it is unknown how many miRNA and genes from them participate in the development of atherosclerosis (Byrne et al, 2014;Toba et al, 2014;Lu et al, 2018;Liu et al, 2020;Shi et al, 2020). As a rule, in publications several miRNA and some candidate genes are studied, so the combination of such attempts is large (Wang C. et al, 2020;Wang M. et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al indicated that miR-377-3p inhibited atherosclerosis-associated vascular smooth muscle cell proliferation and migration through targeting neuropilin2 [ 19 ]. Liu et al demonstrated that PRDM16 upregulation induced by miR-448 inhibition alleviates atherosclerosis via the TGF-beta signaling pathway inactivation [ 20 ]. It was indicated that miR-552 was tightly involved in the development of different kinds of cancers.…”
Section: Discussionmentioning
confidence: 99%